Cognitive aspects of driving in Malaysia : perception and judgement - Lee, Yee Mun (2016)
Malaysia has a worrying road fatality rate compared to many other countries, and the high number of registered motorcycles (vulnerable road users) in the country is one of its most distinctive characteristics. However there has previously been limited experimental research on driving conducted in Malaysia. This thesis aimed to investigate Malaysian drivers’ ability to perceive other road users (cars and motorcycles) and how they make judgments about the safety of pulling out at junctions. Malaysian drivers’ performance in these tasks was compared with UK drivers (Chapter Two). Various studies were also conducted to investigate how different factors affect drivers’ perception and judgment, such as time of day and use of headlights (Chapter Three), a honking sound (Chapter Four), motion and speed (Chapter Five). Chapter Six went on to investigate drivers’ ability to judge the intention of other road users.